THE EFFECT OF DIGITAL FLASHCARD IMPLEMENTATION ON VOCABULARY MASTERY AMONG GRADE 11 STUDENTS AT SMAN 1 SINGARAJA - Laba, Luh Nityaswari; Padmadewi, Ni Nyoman; Dewi, Kadek Sintya (Universitas Suryakancana, 2025)
This study aims to measure the effect of implementing digital flashcards on the mastery of lessons in english education language of 11th grade students at SMAN 1 Singaraja. This study is part of a quasi-experimental study with a pre-test and post-test experimental design and a control group. The population of this study was 395 eleventh grade students at SMAN 1 Singaraja and by simple random sampling, 78 students were selected from two classes that were declared normal and homogeneous as samples. The results showed that the use of digital flashcards significantly improved students' mastery of lessons compared to conventional methods. Pre-test and post-test data were analyzed using a t-test, and it was found that the average post-test score of the experimental group (82.46) was higher than that of the control group (72.19). The significance value obtained (p <0.05) indicated a significant difference in learning outcomes between the two groups. In addition, students in the experimental group showed higher learning motivation and active involvement during learning. This study makes an important contribution to understanding the effectiveness of technology in language learning and provides practical recommendations for educators to improve teaching methods through interactive media.